2014
DOI: 10.1021/np5003498
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Anti-Inflammatory Prenylated Benzoylphloroglucinols and Xanthones from the Twigs of Garcinia esculenta

Abstract: Five new prenylated benzoylphloroglucinol derivatives, garciesculentones A-E (1-5), a new xanthone, garciesculenxanthone A (6), and 15 known compounds were isolated from the petroleum ether extract and the EtOAc-soluble fraction of a 80% (v/v) EtOH extract of Garcinia esculenta. The structures of the new compounds were elucidated by 1D- and 2D-NMR spectroscopic analysis and mass spectrometry. Experimental and calculated ECD and a convenient modified Mosher's method were used to determine the absolute configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 32 publications
(39 reference statements)
1
40
0
1
Order By: Relevance
“…It has been reported in previous studies that traditional Chinese herb Garcinia genus possesses therapeutic effects in cancer treatments (8)(9)(10)(11)(12)(13)15). Therefore, we isolated several PPAPs from the Garcinia genus (7) and tested their effects on breast cancer cell proliferation (Fig.…”
Section: Cambogin Inhibited Proliferation and Induced Apoptosis In Brmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported in previous studies that traditional Chinese herb Garcinia genus possesses therapeutic effects in cancer treatments (8)(9)(10)(11)(12)(13)15). Therefore, we isolated several PPAPs from the Garcinia genus (7) and tested their effects on breast cancer cell proliferation (Fig.…”
Section: Cambogin Inhibited Proliferation and Induced Apoptosis In Brmentioning
confidence: 99%
“…Preliminary experiments indicated that cambogin, as a proapoptotic agent for breast cancer cells, is more potent compared with other PPAPs from Garcinia genus. Cambogin has more effective antitumor effect against breast cells than other compounds in the branches of Garcinia esculenta with high concentrations (11). Cambogin have been demonstrated to possess antitumor activity against medulloblastoma cells (12); however, the active component and the underlying mechanisms remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…G. acuta contains various different components including xanthones, iridoids and triterpenoids (Lv et al, 2009). Modern pharmacological studies have shown that xanthones are the main active compounds of G. acuta and possessed a lot of pharmacological and biological activities such as anti-tumor, protect cardiovascular, hypoglycemic, antioxidant, antibacterial and anti-inflammation activities (Shen et al, 2014;Marona et al, 2008;Ryu et al 2011;Mahendran et al, 2014;Al-Massarani et al, 2013;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous separation process [15], air-dried and powdered plant twigs (4 kg) were extracted with petroleum ether to gain the petroleum ether-soluble S1 portion. The remaining materials were refluxed with 80% EtOH and concentrated to afford a residue.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…G. esculenta Y. H. Li is an endemic plant of China, which is mainly distributed in the western and northwestern part of Yunnan province. To date, there have been only some compounds with cytotoxic and anti-inflammatory properties from this plant reported recently by our groups [15]. 6 suggested a benzylic methylene substituted by oxygen, and its trans-diaxial relationship (J = 7.9 Hz) indicated the occurrence of a trans-substituted 1,4-dioxane ring between the xanthone framework and the phenyl ring, and framed a xanthonolignoid skeleton [17][18][19].…”
mentioning
confidence: 99%